Liberia : Staff Report for the 2002 Article IV Consultation, Overdue Financial Obligations to the Fund-Review Following Declaration of Ineligibility, and Decision on Suspension of Voting and Related Rights. (IMF Staff Country Reports; Country Report ;, 2003)
The civil war in Liberia has resulted in the destruction of most of its infrastructure. Executive Directors noted the weak revenue performance, the lack of progress on fiscal transparency and accountability, and the poor control and prioritization of government spending. They emphasized the need to address governance, accelerate structural reforms, increase revenue, and improve fiscal transparency. In view of all this, Executive Directors agreed that the procedure to suspend Liberia's voting and related rights in the IMF should be initiated.